Conductive polymers: Their preparations and catalyses on NADH oxidation at carbon cloth electrodes - A. Jarjes, Zahraa; Samian, Mohammed Razip; Ab Ghani, Sulaiman (Elsevier, 2015)
This study has made comparison to five such polymers viz. poly (methylene green), poly aniline (PANI), poly (ortho-phenylene diamine) (PoPD), poly (4-vinylpyridine) and poly pyrrole in terms of their preparations and capacities to improve the oxidation of NADH. Cyclic voltammogram showed that all the electrode processes involved in the preparation of the polymers on the carbon cloth electrode are diffusion-controlled. The oxidation of NADH was enhanced when mediated by PANI and PoPD. A fast heterogeneous electron transfer was shown through the increase in anodic peak current together with a decrease in the cathodic peak current.